Microwave-Assisted Metal-Free Synthesis of 2,8-Diaryl-6-aminoimidazo-[1,2-a]pyridine via Amine-Triggered Benzannulation - Nagaraj, Muthupandi; Boominathan, Muthusamy; Muthusubramanian, Shanmugam; Bhuvanesh, Nattamai (Synlett, 2012)
An efficient microwave-assisted metal-free amino benzannulation of aryl(4-aryl-1-(prop-2-ynyl)-1H-imidazol-2-yl)methanone with dialkylamines afforded a variety of 2,8-diaryl-6-aminoimidazo[1,2-a]pyridine in moderate to excellent yield.
Keywords: alkynes; amination; annulation; fused ring systems; heterocycles; green chemistry